2007
DOI: 10.1097/fjc.0b013e31805881ee
|View full text |Cite
|
Sign up to set email alerts
|

Potency and In Vitro Tolerance of Organic Nitrates: Partially Denitrated Metabolites Contribute to the Tolerance-Devoid Activity of Pentaerythrityl Tetranitrate

Abstract: Neither therapeutic dosage of nitrovasodilators nor the development of tolerance correlates with nitrate groups in these molecules. Clinically, low dosages of glyceryl trinitrate (GTN) develop tolerance, but 100-fold higher dosages of pentaerythrityl tetranitrate (PETN) do not. Vasorelaxation was studied on prostaglandian F2alpha (PGF2alpha)-precontracted porcine pulmonary arteries in organ bath procedure. In vitro tolerance was induced by incubating the arteries with different nitrate concentrations and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…4b, table 1). On the other hand, the less potent organic nitrates ISDN and ISMN showed little change in their concentration-relaxation curve upon rechallenge (as reported previously by Koenig et al [25]), suggesting that the induction of clinical tolerance for these compounds may require more time to manifest, for example through some translational and/or transcriptional processes. As with SNP, all three of the cilostazol-based compounds showed a clear right shift of the concentration-relaxation curve upon rechallenge ( fig.…”
Section: Effect Of Repeated Challenges Of the New Organic Nitrate Dermentioning
confidence: 62%
“…4b, table 1). On the other hand, the less potent organic nitrates ISDN and ISMN showed little change in their concentration-relaxation curve upon rechallenge (as reported previously by Koenig et al [25]), suggesting that the induction of clinical tolerance for these compounds may require more time to manifest, for example through some translational and/or transcriptional processes. As with SNP, all three of the cilostazol-based compounds showed a clear right shift of the concentration-relaxation curve upon rechallenge ( fig.…”
Section: Effect Of Repeated Challenges Of the New Organic Nitrate Dermentioning
confidence: 62%
“…The present study extends our previous results on organic nitrate bioactivation and tolerance mechanisms (Munzel et al., 2005a; Daiber et al., 2008). We have shown that a clear correlation between the number of nitrate (‐ONO 2 ) groups in the molecule and the vasodilator potency exists (Koenig et al., 2007a; Wenzel et al., 2007b). Moreover, we demonstrated that potency correlates with the induction of the formation of mitochondrial ROS (Daiber et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have demonstrated that organic nitrate potency correlates with the number of nitrate groups and that high potency nitrates with pD 2 ‐values >6 [pentaerithrityl tetranitrate (PETN), GTN and pentaerithrityl trinitrate (PETriN)] are bioactivated by ALDH‐2 (Daiber et al. , 2004; Koenig et al. , 2007a; Wenzel et al.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable exception seems to be PETN [72]. Some of these effects are related to special pharmacokinetics of PETN [73, 74], but, upon chronic administration, PETN also induces antioxidant pathways at the genomic level and cardioprotective genes (e.g., Apex1 and NFAT5) [75]. Among these induced antioxidant genes are heme oxygenase-1 (HO-1) and ferritin [76], both possessing highly protective properties.…”
Section: Organic Nitratesmentioning
confidence: 99%